2020
DOI: 10.1177/0300891620977010
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between lncRNA DANCR and miR-125b-5p in HCC cell progression

Abstract: Objective: To investigate the mechanism of long noncoding RNA (lncRNA) DANCR on the progression of hepatocellular carcinoma (HCC) cells. Methods: The expression levels of DANCR and miR-125b-5p were measured in normal hepatocytes (LO2) and HCC cell lines by quantitative reverse transcription polymerase chain reaction. HepG2 and Huh-7 cells were transfected with sh-DANCR, the negative control (sh-NC), miR-125b-5p mimic, or mimic NC or cotransfected with sh-DANCR and miR-125b-5p inhibitor. HCC cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…These data revealed that DANCR downregulation could efficiently reduce the inflammatory response and oxidative stress during AS progression, contributing to our understanding of the pathogenic mechanism during AS development. In addition, DANCR has been identified as the ceRNA of several target miRNAs other than miR-214-5p, such as miR-185-5p [32], miR-874-3p [33], miR-1301-3p [34], miR-185-5p [35], miR-345-5p [36], miR-125b-5p [37], and miR-144-3p [38]. Since one lncRNA might target one or more downstream miRNAs [39], we hypothesized that DANCR might also have other target miRNAs that participated in the function of this lncRNA in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…These data revealed that DANCR downregulation could efficiently reduce the inflammatory response and oxidative stress during AS progression, contributing to our understanding of the pathogenic mechanism during AS development. In addition, DANCR has been identified as the ceRNA of several target miRNAs other than miR-214-5p, such as miR-185-5p [32], miR-874-3p [33], miR-1301-3p [34], miR-185-5p [35], miR-345-5p [36], miR-125b-5p [37], and miR-144-3p [38]. Since one lncRNA might target one or more downstream miRNAs [39], we hypothesized that DANCR might also have other target miRNAs that participated in the function of this lncRNA in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…DANCR could act as sponges for multiple miRNAs including miR-216a-5p , miR-27a-3p , miR-125b-5p (Yang et al, 2020), miR-140-3p (Wen et al, 2020) and miR-222-3p (Wang X. et al, 2020) in HCC. DANCR could also stabilize PSMD10 (Liu et al, 2020a) and CTNNB1 (Yuan et al, 2016) mRNAs by binding to their 3 UTR region to prevent its degradation by miRNAs.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Both interventions could also inhibit migratory potential and invasiveness of these cells. Mechanistically, DANCR facilitates progression of this cancer through sponging miR-125b-5p and activating MAPK pathway [ 15 ]. DANCR could also contribute in the liver carcinogenesis through sponging miR‐216a‐5p and surging expression of KLF12 [ 16 ].…”
Section: Cell Line Studiesmentioning
confidence: 99%
“…DANCR indices ubiquitination of FOXO1 via interacting with FOXO1. PID1 promoted by FOXO1 enhances the chemotherapy sensitivity of GBM cells [ 61 ] miR-125b-5p/MAPK pathway axis HepG2 and Huh-7 cells ∆ DANCR: ↓ migration, invasion [ 15 ] Hepatocellular carcinoma miR-216a-5p/KLF12 axis Huh7, HepG2 and LO2 cells ∆ DANCR: ↓ proliferation, migration, invasion and ↑ apoptosis [ 16 ] miR-222-3p/ ATG7 axis Bel7407, Hep3B, HepG2, Huh7, MHCC97H and LO2 ∆ DANCR: ↓ proliferation and autophagy [ 17 ] PSMD10-IL-6/STAT3 signaling axis HEK-293T, Huh7 and Hep3B DANCR promotes sorafenib resistance via PSMD10-IL-6/STAT3 signaling axis [ 18 ] CTNNB1 HCC cells DANCR is involved in stemness features of hepatocellular carcinoma by derepression of CTNNB1 [ 19 ] miR-27a-3p/ROCK1/LIMK1/COFILIN1 pathway axis MHCC‐97H, Huh7, HCC‐LM3, HepG2, MHCC‐97L, Hep3B, SMMC‐7721 and LO2 ∆ DANCR: ↓ proliferation, and metastasis [ 20 ] β-catenin pathway SMMC-7721 and HCCLM3 ∆ DANCR: ↓ proliferation and metastasis [ 62 ] miR-216a BEAS-2B, NCI-H1299, A549, and NCI-H1975 ∆ DANCR: ↓ proliferation and colony formation [ 10 ] Lung cancer miR-1225-3p/ ErbB2 axis 16HBE, A549, SPCA1, H1299 and H1975 ∆ DANCR: ↓ Migration and Invasion [ 11 ] miR-214-5p/CIZ...…”
Section: Cell Line Studiesmentioning
confidence: 99%